MULTIPLE HEMOPARASITIC INFECTIONS IN A DOG: A CASE REPORT - Putri Nur Widyasari; Tetty Barunawati Siagian (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Tick-borne hemoparasitic infections are common health problems in dogs in tropical regions and may occur concurrently, resulting in clinical disorders and complex hematological changes. This case study aimed to describe the clinical findings, laboratory examination results, therapy, and recovery response in a dog with recurrent multi-infection involving Anaplasma spp., Babesia spp., and Ehrlichia spp. This study was conducted descriptively through case-based selection of a nine-year-old male Shih Tzu examined at Piara Pet Care. The examinations included physical evaluation, rapid test kit (A Pet Care), peripheral blood smear, and hematological analysis using an automatic hematology analyzer (Mindray BC-2800 Vet). The results showed positive reactions to Anaplasma spp. and Ehrlichia spp. and a weak positive result for Babesia spp., accompanied by normocytic hypochromic anemia and thrombocytopenia. Causative therapy in the form of doxycycline and imidocarb dipropionate was combined with supportive therapy (Asering, Hematodin, Cyproheptadine, Neuro Forte, Xepazym, Lacto B, and ursodeoxycholic acid) and administered for three weeks. At the end of therapy, the clinical condition and hematological parameters improved. The patient was clinically recovered in the third week, with a recommendation for follow-up parasitological examination to confirm the elimination of the hemoparasitic agents.